Renaissance emblem books. Issue 2 (3rd April 2017) - Pettersson, Rune
Abstract: Emblem books are the result of conscious work to mediate messages using combinations of words, images, and forms. It seems that some of the early work during the Renaissance is in good concert with aesthetic and functional principles of contemporary information design.